Predicting Factors of Health Literacy in Patients with Type 2 Diabetes Mellitus, Uttaradit Province - Faungfoo, Kanjana; Chuleekorn Danyuthasilpe; Aumporn Lincharoen (NU Journal of Nursing and Health Sciences, 2022)
The purpose of this predictive correlational research study was to study factors predicting health literacy among patients with type 2 diabetes mellitus, in Uttaradit Province. There were 200 patients with type 2 diabetes mellitus participating in the study, aged 30 years and older, who were selected by multi-stage random sampling. The research instruments used, showing the reliability of Cronbach’s alpha coefficient, included a perception of health status questionnaire (0.87), a social support questionnaire (0.91), an effective communication questionnaire (0.92), and a health literacy questionnaire (0.96), and they had all been tested for content validity with a score of 0.90. The data were analyzed by descriptive statistics and enter regression analysis. The results revealed that health literacy was at a moderate level ( = 104.12, S.D. = 19.50). Perception of health status, social support and effective communication were found as good combine predictions of health literacy among the patients, with 59.1% of variance (R2 = .591, p < .001). These results suggest thatcommunity nurse practitioner should concern effective communicationand social support in order to promote better awareness of health behavior and to enhance health literacy among patients with type 2 diabetes mellitus